Making everyone`s job easier. How do data scientists fit as a critical member of integrated support teams? - Windt, J.; Taylor, D.; Little, D.; Sporer, B. C. (British Journal of Sports Medicine, 2021)
As technological advances abound and a tidal wave of data hits the sporting world`s shore, the demand for organisations to hire professionals who can reliably collect, integrate and analyse these data continues to rise. Sports biostatisticians have recently been promoted as integral members within sport science and sport medicine teams. Although data-focused professionals may work as a `sports biostatistician`, `data analyst`, `sport scientist`, `performance analyst` or more, we will use `data scientist` for consistency. Regardless of their specific title, common responsibilities for these professionals may include applying data management and analysis skillsets to athlete monitoring, building efficient data collection tools, analysing data for scouting/recruitment, performance analysis, epidemiological reporting and more. As a foundation, data scientists may build or maintain a data infrastructure to support these processes. As an end-product, they provide decision-support systems that inform and audit decisions made across departments. The benefits that such decision-support systems provide and their ability to outperform single humans` decision-making in many realms has been reviewed elsewhere, underscoring the value of data scientists within sport. What remains to be clearly outlined in the literature is how these individuals fit within integrated support teams.